Circulating CD4+ and CD8+ T cells are activated in inflammatory bowel disease and are associated with plasma markers of inflammation. Issue 1 (12th August 2013) - Funderburg, Nicholas T.; Stubblefield Park, Samantha R.; Sung, Hannah C.; Hardy, Gareth; Clagett, Brian; Ignatz‐Hoover, James; Harding, Clifford V.; Fu, Pingfu; Katz, Jeffry A.; Lederman, Michael M.; Levine, Alan D.
Summary Inflammatory bowel disease (IBD) is characterized by damage to the gut mucosa and systemic inflammation. We sought to evaluate the role of chronic inflammation on circulating T‐cell activation in human subjects with Crohn's disease and ulcerative colitis. We studied 54 patients with IBD and 28 healthy controls. T‐cell activation and cycling were assessed in whole blood samples by flow cytometry. Levels of lipopolysaccharide (LPS) were measured in serum by Limulus amoebocyte lysate assay, and plasma levels of inflammatory markers and LPS‐binding proteins were measured by ELISA. The proportions of circulating CD4+ and CD8+ T lymphocytes in cycle (Ki67+) are increased in patients with IBD compared with these proportions in controls. CD8+ T cells from patients with IBD are also enriched for cells that expressed CD38 and HLA‐DR, and proportions of these cells are related to plasma levels of interleukin‐6 and C‐reactive protein in these patients. Intracellular interleukin‐2 and interferon‐γ levels were elevated in resting and polyclonally activated CD4+ and CD8+ T cells in patients with IBD when compared with levels from healthy controls. Surprisingly, we did not find increased levels of LPS in the serum of patients with IBD. We did, however, find a signature of recent microbial translocation, as levels of LPS‐binding protein are increased in the plasma of patients with IBD compared with plasma levels in healthy controls; LPS‐binding protein levels are also directly related to proportions of CD38 HLA‐DR‐expressing CD4+ and CD8+ T cells. Local damage to the gastrointestinal tract in IBD may result in systemic inflammation and T‐cell activation.